No more pumpkins - Catalanotto, Peter; Schembri, Pamela (New York : Henry Holt, 2007)
Second-grader Emily is tired of pumpkins being at the center of every lesson in school, but she is not prepared when a jealous friend damages the jack-o-lantern portrait Emily made for Open House.
Keywords: Pumpkin -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Schools -- Fiction; Behavior -- Fiction